Assess of Forensic Tools on Android Based Facebook Lite with the NIST Method - Bintang, Rauhulloh Noor; Umar, Rusydi; Yudhana, Anton (Scientific Journal of Informatics, 2021)
Purpose: The increase in social media use of Facebook lite by using Android-based smartphones is quite high. Activities when communicating through the social media network Facebook Lite. Facebook lite can send a text message, image, or video. Not a few Facebook users lite social media abusing this app to commit fraud crimes, pornographic acts, or defamation actions from social media users Facebook lite. In such cases, it can be a digital forensic benchmark to get results from digital evidence from the Facebook lite application. Methods: In this investigation, National Institute of Standards and Technology (NIST) research methods with various stages, namely Collection, Examination, Analysis, and Reporting. Result: Comparison and results of data conducted with forensic tools Magnet Axiom Forensic and MOBILedit Forensic Express Pro in the form of parameter data specified. Axiom Forensic Magnet data is 57.14%, while MOBILedit Forensic Express Pro data is 85.71%. Novelty: This data is the data of the performance results of both forensic tool applications in obtaining digital evidence on Facebook lite application.